Supplementary LED Interlighting Improves Yield and Precocity of Greenhouse Tomatoes in the Mediterranean - Paucek, Ivan; Pennisi, Giuseppina; Pistillo, Alessandro; Appolloni, Elisa; Crepaldi, Andrea; Calegari, Barbara; Spinelli, Francesco; Cellini, Antonio; Gabarrell, Xavier; Orsini, Francesco; Gianquinto, Giorgio (Agronomy (Basel), 2020)
In Northern Europe, the use of light–emitting diodes (LEDs) is widely adopted in protected horticulture, enabling to enhance plant growth by ensuring needed radiative fluxes throughout seasons. Contrarily, the use of artificial lighting in Mediterranean greenhouse still finds limited applications. In this study, the effects of supplemental LED interlighting on vegetative development, fruit growth, yield, and fruit quality of high-wire tomato plants (Solanum lycopersicum L. cv. ‘Siranzo’) during spring and summer season were addressed in a hydroponic greenhouse in Italy. Plants were either grown under natural solar radiation (control), or by adding supplemental LED interlighting. LED treatment featured red (R) and blue (B) light (RB ratio of 3) and a photosynthetic photon flux density of 170 µmol m−2 s−1 for 16 h d−1. Supplemental LED interlighting enhanced yield as a result of increased fruit weight and dimension. While no effects on soluble solids content and fruit color at harvesting were observed, supplemental LED interlighting accelerated ripening by one week in spring and two weeks in summer and this also resulted in increased cumulated productivity (+16%) as compared to control treatment. Overall, supplemental LED interlighting can represent a feasible technology for tomato greenhouse production also in the Mediterranean region.